Integrative metagenomics and structural bioinformatics identify explainable gut microbial variants associated with Crohn’s disease - Nadeem Khan; Muhammad Muneeb Nasir; Ubair Aziz; Haseeb Manzoor; Muhammad Faheem Raziq; Zamir Hussain; Ishrat Jabeen; Masood Ur Rehman Kayani (PLoS ONE, 2026)
Metagenomics has revealed disease-associated shifts in microbial taxa and functions in inflammatory bowel disease (IBD) patients. However, the role of genomic variation in gut commensals remains poorly understood. Here, we integrated metagenomic profiling, variant calling, and structural bioinformatics to identify disease-associated variants in the gut microbes. Crohn’s disease (CD) and ulcerative colitis (UC) showed significant negative associations with Bacteroides uniformis , Bacteroides vulgatus , and Eubacterium rectale . These bacteria exhibited 190,712 single-nucleotide polymorphisms, including 479 CD-specific and 235 UC-specific variants. Variant prioritization identified a CD-specific Val170Leu substitution in the conserved starch-binding domain of the Starch Utilization System D (SusD) protein in B. uniformis . Structural modeling and cyclodextrin docking indicated reduced binding affinity in the mutant, while 200-ns molecular dynamics simulations showed stable ligand retention only in the wild type. These findings suggest that impaired starch metabolism driven by SusD variation may contribute to B. uniformis depletion in CD and demonstrate the value of integrating metagenomics with structural analyses to identify functionally relevant microbial variants.